Caracterização biológica de tripomastigotas de T. cruzi provenientes de células deficientes em LAMP - Anny Carolline Silva Oliveira (2017)
Trypanosoma cruzi is the etiological agent of Chagas' disease, a neglected tropical disease of great epidemiological importance. T. cruzi enters the host cells interacting with its surface and causing lesions on its membrane. The latter leads to a process of compensatory endocytosis that culminates with the internalization of this parasite. In previous studies, we have shown that the absence of two lysosomal membrane proteins, LAMP-1 and 2 interferes with the entry of T. cruzi and their growth within the host cells. Inside LAMP-deficient cells, parasite intracellular multiplication rates are much higher than that observed in wild-type cells. In order to investigate whether LAMP-deficient intracellular environment would alter parasite’s characteristics, we infected wild-type and LAMP-1 and/or LAMP-2 deficient fibroblasts and evaluated the rates of invasion and cell adhesion in wild-type LAMP and LLC-MK2 cells, as well as their ability to injure cells. Our results showed that, for wild-type fibroblast cultures, parasites derived from LAMP-1 and 2 or only from LAMP-2 deficient cells differ in their invasion rate, as well as when compared to wildtype derived parasites. We also demonstrated that these differences were not related to the ability of these parasites to adhere to the host cell, which was corroborated by assays performed on an epithelial cell line, LLC-MK2. On the other hand, differences in invasion rates were influenced by the ability of these parasites to cause cellular lesions and induce calcium signals. We believe that the LAMP deficient intracellular environment is able to modify the expression of surface proteins of the parasite, affecting positively or negatively their success in cellular invasion. This hypothesis is corroborated by preliminary studies of the analysis of microvesicles released by the parasites derived from the three cell types studied.